Reality show e teledramaturgia: o drama da vida no Big Brother Brasil 15 - Wanderley, Carolina Pessoa (2016)
Target of criticism from various sections of society, the Big Brother Brazil as object of study, allows looks from various academic aspects such as the Sociology, Anthropology and Psychology, and in the area of communication, can be analyzed from a range of possibilities to deal with the subject example the authors François Jost and Muniz Sodre. Among these possibilities, in this work, he started to study the Big Brother Brazil as televisual product and as a theoretical framework and is considered the television drama elements in order to understand if it is possible to find points of intersection between these two narratives. Therefore, it is important to consider that it is necessary to leave the common sense in which the shows realitys are empty and do not add value to society. As media products such attractions condense aspects involving not only the Brazilian people culture, considering its habits and behavior, but above all, which reconfigures media in a new genre that gives rise to an invented reality, being sold as reality only because it uses real aspects. In this study object of analysis, the construction of the characters worked, observing the physical or behavioral characteristics of the participants that were transmitted by the program production. In the same study, it was also observed that, both in the house parties, as the evidence leader and Angel, the productions performed by the direction of the program can be considered as performing structures from the understanding that such spaces are strategically prepared environments to generate the "stage" of events. The third and most important category of analysis consisted of the construction of three major narrative threads in search of participants to win the program. The first narrative thread refers to the relationship between Amanda and Fernando, the second main narrative thread is the involvement of Aline and Fernando, and the third main narrative thread discusses the lonely path of César Award winner in cash. It is thus understandable that the precise identification of these categories in the fifteenth edition of the reality provides a new perspective on the Big Brother Brazil as audiovisual product. This look not only demystifies the 'label' reality show presented by broadcaster as possible acceptance of television drama elements in this genre programs. Key-words: television; reality show; teledramaturgy